Impacts of the Pandemic on the Developmentof Children with ASD: a Systematic Review - Almeida, Amanda Ramos [UNESP]; de OLIVEIRA, Rafaela Machado Ferreira [UNESP]; Mantovani, Heloísa Briones [UNESP]; Rocha, Aila Narene Dahwache Criado [UNESP] (FapUNIFESP (SciELO), 2023)
Children and teenagers with Autism Spectrum Disorder (ASD) have clinical characteristics that can lead them to challenges in understanding and participating in the new world context and they are more likely to suffer the impacts caused by the COVID-19 pandemic. In this sense, the goal of this study was to analyze whether the pandemic has had an impact on children and teenagers with ASD. This is a systematic review carried out in the electronic databases PubMed, DOAJ, BVS, SciELO and Oásis. Only studies that had children and teenagers with ASD were included. After the searches, a total of 28 articles were included for review analysis. The results show that aspects related to behavior, mental health, routine, interruption of face-to-face attendance and family and school context had greater negative impacts, while communication and socialization had positive impacts. Not many studies were identified regarding the impacts of the pandemic on the motor aspects and the change of calls to telemonitoring. It is concluded that the pandemic caused significant impacts on children and adolescents with ASD, so, with the resumption of face-to-face activities, this audience will need more attention.
Impactos da Pandemia no Desenvolvimento da Criança com TEA: uma Revisão Sistemática
Keywords: Autism Spectrum Disorder; Childhood; Impacts of the pandemic; COVID-19; Occupational Therapy